Melepaskan Beban Menghadapi Kekhawatiran Menurut (1 Petrus 5:7) - Fidenius Laia; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Anxiety is a serious problem in human life. Anxiety can paralyze the soul so that a person can lose the enthusiasm to do something. Worry can damage a person's relationship with someone, even with God. Worry is also a feeling of worry, anxiety. Worry is being afraid (anxious, worried) about something that is not yet known for certain. Feelings of worry or anxiety not only affect physical health, but in daily life practices influence the patterns of thinking and spirituality that are built. Worrying cannot solve our problems. Worrying doesn't help tomorrow's troubles, but it completely destroys today's happiness. The more we worry, the more difficult and difficult the life we ​​live.